2016
DOI: 10.1007/s00253-016-7804-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on antimicrobial agents of the terrestrial Streptomyces sp. BCC71188

Abstract: The terrestrial actinomycete strain BCC71188 was identified as Streptomyces by its morphology (having spiral chain spore on the aerial mycelium), chemotaxonomy (containing LL-diaminopimelic acid in the cell wall), and 16S rRNA gene sequence analysis [showing high similarity values compared with Streptomyces samsunensis M1463 (99.85 %) and Streptomyces malaysiensis NBRC 16446 (99.40 %)]. The crude extract exhibited antimalarial against Plasmodium falciparum (IC 0.19 μg/ml), anti-TB against Mycobacterial tubercu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…Elaiophylin ( 2 ) inhibited both the 3D7 and Dd2 parasites with similar potency, IC 50 = 778 nM and 598 nM, respectively. Antiplasmodial activity in the same range (IC 50 214 nM) against the K1 strain was previously reported in the literature [ 26 ]. Herbimycin G showed no cytotoxicity and some degree of parasite growth inhibition, corresponding to a 77% inhibition against 3D7 at 40 μM.…”
Section: Resultssupporting
confidence: 71%
“…Elaiophylin ( 2 ) inhibited both the 3D7 and Dd2 parasites with similar potency, IC 50 = 778 nM and 598 nM, respectively. Antiplasmodial activity in the same range (IC 50 214 nM) against the K1 strain was previously reported in the literature [ 26 ]. Herbimycin G showed no cytotoxicity and some degree of parasite growth inhibition, corresponding to a 77% inhibition against 3D7 at 40 μM.…”
Section: Resultssupporting
confidence: 71%
“…GM, previously isolated from Streptomyces hygroscopicus , is a benzoquinone antibiotic containing the typical structures of benzoquinone and dienamide. This class of compounds showed various bioactivities, including anticancer, anti-protozoa, antimalarial and antifungal activities [ 34 , 35 ]. Based on extensive investigation of the literatures and the analyses of UPLC-MS data, it is concluded that these compounds with HR-ESI-MS [M − H] − 547.2805 (retention time at 8.0 min), 533.2992 and 547.2636 (retention time at 12.0 min) are very likely novel GMs produced by the strain XY-FW47 (see Figure S10 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two benzoquinone polyketides, geldanamycin ( 409 ) and 17-demethoxyreblastatin ( 410 ), were isolated from the extract and showed antiplasmodial activity against the K1 strain. The quinone moiety in 409 appears to contribute to the cytotoxicity since the structural analogue 410 with a phenol group instead of the quinone was more selective against the parasite [254]. Two new antiplasmodial azaphilones, longirostrerone A ( 411 ) and C ( 412 ), were isolated from the ethyl acetate extract of the Thailand soil fungus Chaetomium longirostre .…”
Section: Quinones and Polyketidesmentioning
confidence: 99%